2016
DOI: 10.1089/dna.2016.3437
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Level of Klotho Contributes to Drug Resistance in Lung Cancer Cells: Involving in Klotho-Mediated Cell Autophagy

Abstract: Klotho is originally discovered as an anti-aging gene and recently identified as a tumor suppressor in various human cancers. Drug resistance is a major obstacle to affect the treatment of chemotherapy. In the present study, we explore the role of klotho on drug resistance in human lung cancers and investigate the mechanism of klotho on drug resistance in lung cancer cells. First, we detected a panel of six human lung cancer cell lines, including H460, SK-MES-1, cisplatin (DDP)-resistant A549/DDP, its parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…The association between Klotho and autophagy has been reported in various diseases, such as Alzheimer's disease, acute kidney injury, chronic obstructive pulmonary disease, and lung cancer (12)(13)(14)(15). These findings suggest that Klotho has an important role in the pathogenesis of those diseases.…”
mentioning
confidence: 78%
“…The association between Klotho and autophagy has been reported in various diseases, such as Alzheimer's disease, acute kidney injury, chronic obstructive pulmonary disease, and lung cancer (12)(13)(14)(15). These findings suggest that Klotho has an important role in the pathogenesis of those diseases.…”
mentioning
confidence: 78%
“…The tumor suppressive function of Klotho has been reported in several human solid malignancies, but less in hematological cancers, especially in lymphoma (16)(17)(18)(19). Lower Klotho expression was detected in T-cell lymphoma tissues whereas high expression level of Klotho was observed in normal lymph (17,20,21). Additionally, Klotho decline has a significant prognostic value in cancers, such as large cell neuroendocrine carcinoma (LCNEC), small cell lung cancer (SCLC) and hepatocellular carcinoma (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…docetaxel resistance is a critical issue in treating advanced nSclc, and its potential underlying mechanisms have been elucidated, including the implication of intracellular multidrug resistance-associated protein P-glycoprotein, lung resistance protein, glutathione transferase and t-structural changes of intracellular microtubules topoisomerase (26). In addition, it has been reported that high-mobility group box 1-mediated autophagy contributes to docetaxel resistance in lung adenocarcinoma (27), while another study revealed that Klotho-mediated autophagy was closely involved in chemotherapy resistance (including docetaxel resistance) in lung cancer (28). in the present study, it was also demonstrated that autophagy attenuated the cytotoxic effects of docetaxel on a549/dTX cells, which was in line with these previous findings.…”
Section: Docetaxel Group Apatinib Plus Docetaxel Group --------------mentioning
confidence: 99%